EFEKTIVITAS MODEL PEMBELAJARAN BERBASIS (PROJECT BASED LEARNING) BERBANTUAN PHET TERHADAP PENINGKATAN PENGUASAAN KONSEP RANGKAIAN LISTRIK SEDERHANA PADA SISWA SEKOLAH DASAR - Deric Wisnu Pradana; Sholikhan, Sholikhan; Farida Nur Kumala (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effectiveness of the Project-Based Learning (PjBL) model assisted by PhET simulations in improving elementary school students’ concept mastery of simple electrical circuits. This research employed a quantitative approach with a quasi-experimental design using the nonequivalent control group design. The sample consisted of an experimental class (VA) with 30 students taught using PjBL assisted by PhET and a control class (VB) with 30 students taught using conventional learning. Data were collected using pretest and posttest instruments consisting of 15 multiple-choice questions and 5 essay questions. Data analysis was conducted using the One-Sample Kolmogorov-Smirnov Test normality test, Levene homogeneity test, and independent sample t-test with SPSS 30. The results indicate that the PhET-assisted PjBL model significantly improves students’ concept mastery compared to conventional learning.